Application of Machine Learning Methods in Customer Satisfaction Measurement based on Online Comments - Thai Kim , Phung; Nguyen An , Te (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study proposes the application of a machine learning method to measure customer satisfaction based on online comments. Research data is the reviews of travelers on Agoda.com about hotels in Vietnam. The study conducts training using machine learning models: Neural Network (NN), Decision Tree (DT), Naïve Bayes (NB), Support Vector Machines (SVM), Logistic Regression (LR), and Random Forest (RF) to find the best classification model, then apply this model to predict the customer satisfaction classification across the entire dataset. Next, the study uses the method of aggregating and ranking customer satisfaction. This study has reference value for measuring customer satisfaction in business fields.
Keywords: Machine learning; Satisfaction measurement; Opinion mining